PEMBERDAYAAN MASYARAKAT DALAM PEMBUATAN HAND SANITIZER BERBASIS KEARIFAN LOKAL EKSTRAK DAUN CENGKEH - Prodyanatasari, Arshy (Universitas Bakti Tunas Husada, 2024)
The Covid-19 pandemic that hit all countries, including Indonesia, resulted in major changes, especially in the health sector. There is an appeal for social distancing and also more health consciousness such as washing hands or using hand sanitizer every time you want to and after activities, such as eating. Washing hands or using hand sanitizer aims to kill bacteria and viruses. The use of hand sanitizer can be a solution if there is no clean water that is easily accessible or more practical to use wherever you are. However, with the increasing need for hand sanitizers, there is a scarcity of hand sanitizers on the market. This requires the community to be creative in finding solutions to the scarcity. One of the efforts that can be made is to make a hand sanitizer based on local wisdom of clove leaf extract, where Blimbing Village has natural products of clove leaf extract that have not been optimally utilized. In this community empowerment PkM activity, residents are given education about the benefits, and how to use, and make hand sanitizers. In Mini PkM activities, the results showed that residents were enthusiastic about participating in PkM activities and were able to make hand sanitizers using available materials well, as well as an increase in knowledge about hand sanitizers. The increase in residents' knowledge can be seen from the statistical analysis of the pretest and posttest results. Based on the above, it can be concluded that community empowerment in making hand sanitizers based on local wisdom of clove oil extract can increase residents' knowledge and can be an alternative amid the scarcity of hand sanitizers on the market.